Effects of Front Desk Staff Service Quality on Customer Satisfaction in Some Selected Hotels in Tamale Metropolis - Alhassan, Shafawu; Bariham, Iddrisu; Olu, Ellen Louisa (Advances in Social Sciences Research Journal, 2024)
The hotel sub-sector provides a plethora of services to stimulate the growth of the tourism sector. As a result, numerous governments offered a lot of incentives to support the growth of the hotel businesses in Ghana. However, it seems most of the hotels in the hospitality industry including those in Tamale Metropolis are not meeting the quality standards expected of them in connection with service delivery, good customer relationships, sufficient facilities, and provision of confidence and trust of services offered. The study, therefore, examined the effects of front desk staff service quality on customer satisfaction in some selected hotels in Tamale Metropolis. The SERVQUAL Model served as the study's foundation. The study employed cross-sectional survey design. Multi-stage sampling strategy was used. A convenient sampling approach was employed to select the 2 hotels in the Metropolis for the research. Statistical Package for Social Sciences (SPSS) version 22 was used to analyze the data. The study found that guests had a positive perception of front desk staff at the two hotels. However, most of the guests did not have confidence that front desk staff inspire visitors, and that information about the two hotels was not sufficiently available. It was further revealed that front desk staff service quality significantly affects customer satisfaction. However, treatment equality, attention to details, and front desk staff language proficiency were the factors the front desk staff lack. The study recommends hoteliers engage highly motivated front desk staff; capacity building of front desk staff on how to inspire visitors to attract more customers; and training of front desk staff on how to be more attentive to guests' needs and preferences in order to improve the guest stay and overall experience.